The health and economic impacts of exposure to marine mobile emissions from ships in Durban port, South Africa - Manqele, Nkosinathi M.; Moolla, Raeesa; Ramsay, Lisa Frost (Atmospheric Environment: X, 2024)
South Africa remains an uncharted realm in terms of marine mobile emissions inventory and hence the impact of pollution from ships in coastal cities remains unknown. Such a void creates uncertainties about the extent of population exposure to pollution from ships, the health impact and economic value associated with the changes in policies for the port city of Durban. This study was aimed at estimating the health and economic impact of marine mobile emissions and the health and economic benefits associated with improvement in air quality within the port city of Durban, which is under eThekwini municipality. The population exposure to particulate matter of less than 2.5 and 10 μm (PM2.5 and PM10) and sulphur dioxide (SO2) from ships calling into Durban port were estimated using the AERMOD air dispersion model. The BenMAP modelling tool was then used to estimate the health impact and economic value of changes in emission of PM2.5, PM10 and SO2 from ships visiting Durban port. The reduction in emissions from ships was due to the reduction in the sulphur content of fuel from 3.5% to 0.5% that was implemented by the International Maritime Organisation (IMO) on the 01st of January 2020. The results showed that PM2.5 and PM10 emissions reduced by 63% in 2020 compared to 2018, whilst SO2 emissions reduced by 82% over the same period. The BenMAP results indicated that 49 premature mortalities were avoided in 2020 compared to 2018 since the IMO's forced reduction in sulphur content of fuel by 85% in 2020. These avoided cases on mortality were estimated a monetary value of R228 million using the World Bank’s 2016 estimates and R683 million using the USEPA Mean VSL estimate. Such monetary values were respectively equivalent to 0.05% and 0.2% of the eThekwini's GDP, which was estimated at R468 billion in 2016.